A Weight and Meta-Analysis on the Academic Achievement of High School Students - Nunes, Catarina (2022)
Nunes, C., Oliveira, T., Santini, F. D. O., Castelli, M., & Cruz-jesus, F. (2022). A Weight and Meta-Analysis on the Academic Achievement of High School Students. Education Sciences, 12(5), 1-17. [287]. https://doi.org/10.3390/educsci12050287